Factors Associated With Care Workers' Intention to Leave Employment in Nursing Homes: A Secondary Data Analysis of the Swiss Nursing Homes Human Resources Project. (November 2019) - Gaudenz, Clergia; De Geest, Sabina; Schwendimann, René; Zúñiga, Franziska
The emerging care personnel shortage in Swiss nursing homes is aggravated by high turnover rates. As intention to leave is a predictor of turnover, awareness of its associated factors is essential. This study applied a secondary data analysis to evaluate the prevalence and variability of 3, 984 nursing home care workers' intention to leave. Work environment factors and care worker outcomes were tested via multiple regression analysis. Although 56% of care workers reported intention to leave, prevalences varied widely between facilities. Overall, intention to leave showed strong inverse relationships with supportive leadership and affective organizational commitment and weaker positive relationships with stress due to workload, emotional exhaustion, and care worker health problems. The strong direct relationship of nursing home care workers' intention to leave with affective organizational commitment and perceptions of leadership quality suggest that multilevel interventions to improve these factors might reduce intention to leave.